(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents an analysis of professional development and retraining courses for higher education institution educators aimed at enhancing their digital competencies. From 2021 to 2023, training sessions were conducted under the module "Implementation of Digital Technologies in the Educational Process," and since 2023, under the module "Digital Competencies in Pedagogical Activities." The sessions resulted in a significant improvement in educators’ knowledge. The article highlights the effectiveness of the courses, sector-specific results, and analysis based on an online course platform. Effective approaches to developing digital competencies are proposed as outcomes.